On spatial behavior of the solution of a non-standard problem in linear thermoviscoelasticity with voids - Bucur, A. (Archives of Mechanics, 2015)
In this paper we study the constrained motion of a prismatic cylinder made of a thermoviscoelastic material with voids and subjected to final given data that are proportional, but not identical, to their initial values. We show how certain cross-sectional integrals of the solution spatially evolve with respect to axial variable. Some conditions are derived upon the proportionality coefficients in order to show that the integrals exhibit alternative behavior.